Gender difference and age-related changes in performance at the long-distance duathlon - Rüst, C. A.; Knechtle, B.; Knechtle, P.; Pfeifer, S.; Rosemann, T.; Lepers, R.; Senn, O. (The Journal of Strength and Conditioning Research, 2013)
The differences in gender- and the age-related changes in triathlon (i.e., swimming, cycling, and running) performances have been previously investigated, but data are missing for duathlon (i.e., running, cycling, and running). We investigated the participation and performance trends and the gender difference and the age-related decline in performance, at the "Powerman Zofingen" long-distance duathlon (10-km run, 150-km cycle, and 30-km run) from 2002 to 2011. During this period, there were 2,236 finishers (272 women and 1,964 men, respectively). Linear regression analyses for the 3 split times, and the total event time, demonstrated that running and cycling times were fairly stable during the last decade for both male and female elite duathletes. The top 10 overall gender differences in times were 16 ± 2, 17 ± 3, 15 ± 3, and 16 ± 5%, for the 10-km run, 150-km cycle, 30-km run and the overall race time, respectively. There was a significant (p < 0.001) age effect for each discipline and for the total race time. The fastest overall race times were achieved between the 25- and 39-year-olds. Female gender and increasing age were associated with increased performance times when additionally controlled for environmental temperatures and race year. There was only a marginal time period effect ranging between 1.3% (first run) and 9.8% (bike split) with 3.3% for overall race time. In accordance with previous observations in triathlons, the age-related decline in the duathlon performance was more pronounced in running than in cycling. Athletes and coaches can use these findings to plan the career in long-distance duathletes with the age of peak performance between 25 and 39 years for both women and men.